The Bind that Ties: Socioemotional Wealth Preservation in Family Firms - Gomez-Mejia, Luis R.; Cruz, Cristina; Berrone, Pascual; De Castro, Julio (Academy of Management Annals, 2011)
A growing body of research shows that family firms are different from other organizations in significant ways. In this paper we review this literature by examining how family firms differ from nonfamily firms along five broad categories of managerial decisions. These categories encompass a set of key organizational choices concerning management processes, firm strategies, corporate governance, stakeholder relations and business venturing. We argue that socioemotional wealth or affective endowment of family owners explain many of these choices. We also examine some contingency factors (namely family stage, firm size, firm hazard, and the presence of nonfamily shareholders) that moderate the influence of socioemotional wealth preservation as a point of reference when making managerial decisions in family firms. Lastly, we explore the firm performance consequences of family ownership.